Generalized Dynamic Panel Data Models with Random Effects for Cross-Section and Time - Geert Mesters; Siem Jan Koopman (Tinbergen Institute, 2012)
An exact maximum likelihood method is developed for the estimation of parameters in a nonlinear non-Gaussian dynamic panel data model with unobserved random individual-specific and time-varying effects. We propose an estimation procedure based on the importance sampling technique. In particular, a sequence of conditional importance densities is derived which integrates out all random effects from the joint distribution of endogenous variables. We disentangle the integration over both the cross-section and the time series dimensions. The estimation method facilitates the flexible modeling of large panels in both dimensions. We evaluate the method in a Monte Carlo study for dynamic panel data models with observations from the Student's t distribution. We finally present an extensive empirical study into the interrelationships between the economic growth figures of countries listed in the Penn World Tables. It is shown that our dynamic panel data model can provide an insightful analysis of common and heterogeneous features in world-wide economic growth.
urn:NBN:nl:ui:31-1871/38471
Keywords: C33; C51; F44; 330; Panel data; Non-Gaussian; Importance sampling; Random effects; Student's t; Economic growth; Stochastischer Prozess; Maximum-Likelihood-Methode; Statistische Verteilung; Monte-Carlo-Methode; Schätzung; Wirtschaftswachstum; Welt